(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In modern pedagogy, the problem of "Pedagogical diagnosis" has been studied by various scientists. Based on their experience, scientists have developed pedagogical diagnostic theories.